Enzyme Treatment Improves The Utilization Of Lupin-Based Diets By Japanese Quail (Coturnix Japonica) - Mahmoud Khalil; Irek A. Malecki; Mahmoud El-Attrouny; Graeme B. Martin (The International Journal of Tropical Veterinary and Biomedical Research, 2019)
In poultry, feeding diets including high concentrations of non-starch polysaccharides limits growth rate and feed conversion ratio, and causes problems in health and welfare because of the production of wet droppings. This problem is becoming more important as pressure builds to reduce costs by using alternative sources of dietary protein, such as lupin grain, rather than fish- or soybean-meal. We therefore tested whether enzymes that break down non-starch polysaccharides can overcome the problems with a lupin-based diet fed to Japanese quail. Chicks (18 days old) were allocated among 8 treatments, each replicated 3 times, with 12 chicks per replicate (ie, 36 birds per treatment). Chicks were fed diets formulated to contain 24% crude protein and 12 MJ/kg apparent metabolisable energy (AME). The diets included 10% or 20% lupin meal and, for each level of lupin, they were formulated in one of four ways: 1) no enzyme; 2) pectinase (1.4 U/g polygalacturonase and 0.2 U/g pectinesterase); 3) xylanase (1,4 endo-xylanase; 0.38 U/g); 4) combination of the above pectinase and xylanase treatments. The results indicated that, from age 28 days of age, both lupin content and enzyme treatment significantly (P 0.05) affected chick performance. Compared with the no-enzyme control, enzyme treatments improved growth at 35 days by 45-50% (P 0.05) and feed conversion ratio by 20-30% (P 0.05) for both levels of lupin content. In addition, dry matter digestibility and apparent metabolizable energy were significantly improved by the combined enzyme treatment for both levels of lupin inclusion. We conclude that pectinase and xylanase can overcome the negative effects of the non-starch polysaccharides in lupin meal, improving the growth of quail chicks fed lupin-based diets, and that the enzymes work best when combined.